Foreword: Honouring Anthony Angelo's Contribution - Atkin, Bill; Butler, Petra; Costi, Alberto; McLay, Geoff (Victoria University of Wellington Law Review, 2008)
This foreword introduces the articles published in this issue which celebrates the life of Professor A H Angelo of the Law Faculty at Victoria University of Wellington and this Law Review. The issue is divided into two parts: the first covering personal reflections concerning Professor Angelo or his subjects, and the second containing pieces by leading scholars that reflect different aspects of Professor Angelo's research and service.